DeSUMOylation switches Kaiso from activator to repressor upon hyperosmotic stress. Issue 11 (November 2018) - Zhenilo, Svetlana; Deyev, Igor; Litvinova, Ekaterina; Zhigalova, Nadezhda; Kaplun, Daria; Sokolov, Alexey; Mazur, Alexander; Prokhortchouk, Egor
Abstract Kaiso is a member of the BTB/POZ zinc finger family, which is involved in cancer progression, cell cycle control, apoptosis, and WNT signaling. Depending on promoter context, it may function as either a transcriptional repressor or activator. Previous studies found that Kaiso might be SUMOylated due to heat shock, but the biological significance of Kaiso SUMOylation is unclear. Here, we find that K42 is the only amino acid within Kaiso that is modified with SUMO. Kaiso is monoSUMOylated at lysine 42 in cell lines of kidney origin under normal physiological conditions. SUMOylated Kaiso can activate transcription from exogenous methylated promoters, wherein the deSUMOylated form of the protein kept the ability to be a repressor. Rapid Kaiso deSUMOylation occurs in response to hyperosmotic stress and is reversible upon return to an isotonic environment. DeSUMOylation occurs within minutes in HEK293 cells treated with 100 mm NaCl and relaxes in 3 h even in a salt-containing medium. Genomic editing ofKaiso by conversion of K42 into R42 (K42R) in HEK293 cells that resulted in fully deSUMOylated endogenous protein led to misregulation of genes associated with ion transport, blood pressure, and the immune response. TRIM25 was significantly repressed in two K42R HEK293 clones. By a series of rescue experiments with K42R and KO HEK293 cells, we show that TRIM25 is a direct transcriptional target for Kaiso. In the absence of Kaiso, the level of TRIM25 is insensitive to hyperosmotic stress. Extending our observations to animal models, we show that in response to a high salt diet, Kaiso knockout mice are characterized by significantly higher blood pressure increases when compared to wild-type animals. Thus, we propose a novel biological role for Kaiso in the regulation of homeostasis.